An Argument for Unbelief: A Discussion about Terminology. (14th December 2018) - Conrad, Nickolas Garth
The rupture with traditional religion and the loss of belief in God as a widespread religious position represents a sea change in Western thought. However, there were very few self-declared atheists, secularists, and humanists in Western history prior to the nineteenth and twentieth centuries and even during the Modern period, there are not many. This is especially true in my own research of nineteenth and early twentieth-century France. Those who took the name of atheist such as Baron d'Holbach or Jacques-André Naigeon were exceptional militants. The quest to find other such atheists buried in the pages and hidden messages of key books is a limited endeavor. Atheism as a concept does not originate from any single creed or doctrine and is itself open to permutation. Looking for a clear and distinct form of atheism is looking for a conceptual phenomenon constructed by the researcher. The language and words we use control and direct how we understand the past. The term "atheist" imposes a rigidity to a fluid and shifting phenomenon. Instead, we should open up our research to the emergence of modern "unbelief, " as defined by Gordon Stein and Tom Flynn in The Encyclopedia of Unbelief . This paper will argue for "unbelief" as the proper analytical category as a field of future research that will allow for a much larger, more inclusive, variegated set of parameters to understand the rupture with traditional forms of religion or spiritual practices. The important change in intellectual history was not the emergence of a particular atheism that promoted scientism and which held to its positions dogmatically but the acute doubt of past intellectual and religious traditions that led to a spectrum of new ideologies and religious positions.